Micro and Macronutrient Availability for Rice Growth on Sandy Soil with Application of Azolla microphylla and Poultry Manure - Jauhari Syamsiyah; Aktavia Herawati; Ganjar Herdiansyah; Atika Sari Damayanti (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Sandy soil has various constraints, such as the low availability of N, P, and K nutrients. Organic matter should be applied to improve soil conditions. This study’s organic materials used as ameliorants included chicken manure and Azolla microphylla. This study aimed to determine the effect of A. microphylla and chicken manure on the availability of micro and macronutrients and rice growth in sandy soil. The research was conducted on the sandy soil of Samas Beach, Bantul, Yogyakarta. The study used a factorial complete randomized block design consisting of 2 factors. The 1st factor is the dose of Azolla (0 and 7.5 tons ha-1). The 2nd factor is the dose of chicken manure (50, 100, 150 tons ha-1). The results showed no interaction between the application of A. microphylla and chicken manure. The application of chicken manure increased NO3-, available P, and available K levels. The application of A. microphylla increased the height of rice plants. Azolla 7.5 tons ha-1 and chicken manure 150 tons ha-1 showed the highest values in NO3- (0.11 mg l-1), available P (6.74 ppm), and organic C (0.27%). Chicken manure of 150 tons ha-1 can increase the number of grains per panicle. These findings offer a potential strategy for addressing nutrient deficiencies in sandy soils and improving rice growth.